HelloTalk: A Review of Internet-Based Software to Support Arabic Vocabulary Mastery - Fuada, Farha; Karima, Salman Rizqan; Rahmawati, Siti Uriana (Department of Arabic Education - Faculty of Educational Sciences, 2023)
One of the important elements of mastering Arabic is memorizing vocabulary. This is because vocabulary is related to the four language skills. The main impediment to learning Arabic motivation is a lack of vocabulary mastery. This study focuses on the description of the HelloTalk application in learning Arabic, especially in teaching vocabulary. This research covers the advantages and disadvantages of the HelloTalk application as a means of learning vocabulary. A qualitative approach and the application of triangulation are used to verify the data obtained. The data collection method used was observation and interviews to investigate the practice of teaching vocabulary in the HelloTalk application. The data analysis technique used in this research uses the Miles and Huberman model, which consists of the processes of data collection, data reduction, data display, and drawing conclusions. The involvement of multiple instruments and participants makes the HelloTalk application review more comprehensive. HelloTalk as a learning tool that is popular and effective in learning vocabulary must be further developed so that the potential for language learning is increased and made more useful.